1988
DOI: 10.1017/s0021859600083659
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reduced leaf shear strength on the nutritive value of perennial ryegrass

Abstract: S U M M A R YProgeny of perennial ryegrass (PRG) plants selected for low and high leaf shear strength were sown in a spaced-plant field experiment and were shown to differ in leaf strength in the same direction, confirming this to be a heritable trait. Selection for low leaf shear strength also reduced weight per leaf length, but had no effect on dry-matter (D.M.) percentage, growth score, rust score or tendency towards aftermath heading.Rates of D.M. consumption (g D.M./min) and ruminal degradation of D.M. us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
2
4

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 13 publications
2
40
2
4
Order By: Relevance
“…Rupture of herbage in chewing is a function of both tensile and shear strength; both are highly heritable traits (Wilson 1965;MacKinnon et al 1988).…”
Section: Anatomy and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of herbage in chewing is a function of both tensile and shear strength; both are highly heritable traits (Wilson 1965;MacKinnon et al 1988).…”
Section: Anatomy and Morphologymentioning
confidence: 99%
“…Shear strength varies with physiological age of leaves so that, for good sampling accuracy, leaves need to be selected for uniform age. Reduced shear strength of ryegrass leaves from plants selected for high and low shear strength is associated with a faster rate of eating but not with fermentation characteristics in situ (MacKinnon et al 1988;Kennedy & Doyle 1993). Thus leaf shear strength has potential for use in selecting perennial ryegrass with increased rates of voluntary intake by ruminants (Henry et al 1993).…”
Section: Anatomy and Morphologymentioning
confidence: 99%
“…Studies to better characterize the quality of forages by their physical properties have considered techniques such as the resistance to grinding (Minson & Cowper, 1974) and to shearing (Mackinnon et al, 1988). Evidence exists that shearing resistance is related to chemical composition, especially to the cell wall and its components (Wilson, 1997;Hughes et al, 2000;Nave et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Higher leaf tensile or shearing force was related to higher concentrations of cellulose (Wilson 1965;Mackinnon et al 1988) and hemicellulose (Mackinnon et al 1988) in perennial ryegrass plants. However, Nguyen et al (1982) and Iwaasa et al (1996a) reported difficulty in establishing a consistent relationships between CW chemical constituents and tensile or shearing force.…”
mentioning
confidence: 97%
“…Weston and Davis (1991) reported shear or comminution energy as the best characteristic of forages to predict constraint to forage intake, and in turn voluntary intake. Differences between forages in their resistance to chewing and removal from the rumen were reflected in shearing force differences in perennial ryegrass leaves (Lolium perenne L.) (Mackinnon et al 1988;Inoue et al 1989). …”
mentioning
confidence: 99%